2014
DOI: 10.1002/jso.23572
|View full text |Cite
|
Sign up to set email alerts
|

Role of miR‐200 family members in survival of colorectal cancer patients treated with fluoropyrimidines

Abstract: miR-200a, miR-200c, miR-141, and miR-429 expression levels may identify CRC patients, including those with stage II disease, who are most likely to benefit from adjuvant chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 33 publications
2
63
1
Order By: Relevance
“…Patients with lower miR-141 were more likely to have systemic lupus erythematosus (14 ). In cancers, higher concentrations of miR-141 in resected colorectal cancer patients were found to be associated with long-term and disease-free survival (15 ), on the one hand, but on the other, and seemingly more consistently, with poor outcomes including biochemical recurrence (16 ), increased metastasis (17 ) in prostate cancer, or poor prognosis in prostate cancer (18 ), hepatocellular carcinoma (19 ), and colon cancer (20 ). Results obtained in an identification cohort supported association of miR-141 with bladder cancer; however, this was not confirmed in a validation cohort (21 ).…”
Section: Diagnostic Specificity and Reproducibility Multiple Associatmentioning
confidence: 98%
“…Patients with lower miR-141 were more likely to have systemic lupus erythematosus (14 ). In cancers, higher concentrations of miR-141 in resected colorectal cancer patients were found to be associated with long-term and disease-free survival (15 ), on the one hand, but on the other, and seemingly more consistently, with poor outcomes including biochemical recurrence (16 ), increased metastasis (17 ) in prostate cancer, or poor prognosis in prostate cancer (18 ), hepatocellular carcinoma (19 ), and colon cancer (20 ). Results obtained in an identification cohort supported association of miR-141 with bladder cancer; however, this was not confirmed in a validation cohort (21 ).…”
Section: Diagnostic Specificity and Reproducibility Multiple Associatmentioning
confidence: 98%
“…Besides, experimental and clinical studies have cleared that hsa-let-7g and hsa-miR-181b are potential indicators for chemoresponse to S-1 based chemotherapy and miR-200a, miR-200c, miR-141, and miR-429 expression levels may identify CRC patients, including those with stage II disease, who are most likely to benefit from fluropyrimidine, an adjuvant chemotherapy agent (Nakajima et al, 2006;Diaz et al, 2014).…”
Section: Mirna As Marker For Treatment Response Predictionsmentioning
confidence: 99%
“…A total of 2,534 patients from the United Kingdom, Germany, Spain, Poland, Japan, Sweden, Korea, Norway, Denmark, Italy, USA, China and Chinese Taiwan were diagnosed with a variety of cancers, including esophageal cancer [12,19,27], gastric cancer [16,25,28], colorectal cancer [8,20,29], rectal cancer [30], hepatocellular carcinoma [26], pancreatic cancer [11], lung cancer [13], breast cancer [15], diffuse large B-cell lymphoma (DLBCL) [18], bladder cancer [10], endometrial cancer [14,17], ovarian cancer [9,21,23,24] and prostate cancer[22]. In the primary reports, 11 studies showed a significant association between high miR-200c and poor prognosis [8,9,13,15,16,17,18,19,20,21,22], 9 provided the opposite result [10,11,24,25,26,27,29,30] and 5 found no prognostic value of miR-200c for tumor patients [12,14,20,23,28]. The expression of miR-200c was most often detected in tumor tissue samples, while five studies tested it in plasma or serum [15,16,19,20,27].…”
Section: Resultsmentioning
confidence: 99%
“…So 18 studies were identified in the 16 articles and were enrolled into the meta-analysis (Fig. 1) [10,11,12,13,14,15,16,17,19,20,22,24,25,27,28,29]. It has been previously reported that there was no association between serum miR-200c and miR-200c in primary tumor tissue [20], thus we performed a meta-analysis based on both tissue and circulating miR-200c independently.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation